One-Year COMBO Stent Outcomes in Acute Coronary Syndrome: from the COMBO Collaboration - Chandrasekhar, Jaya; de Winter, Vera C; Kalkman, Deborah N; Sartori, Samantha; Chandiramani, Rishi; Aquino, Melissa B; de Wilde, Puk; Zeebregts, Doreen; Woudstra, Pier; Beijk, Marcel A; Hájek, Petr; Atzev, Borislav; et al. (Cardiovascular drugs and therapy, 2021)
PURPOSE: The COMBO biodegradable polymer sirolimus-eluting stent includes endothelial progenitor cell capture (EPC) technology for rapid endothelialization, which may offer advantage in acute coronary syndromes (ACS). We sought to analyze the performance of the COMBO stent by ACS status and ACS subtype. METHODS: The COMBO collaboration (n = 3614) is a patient-level pooled dataset from the MASCOT and REMEDEE registries. We evaluated outcomes by ACS status, and ACS subtype in patients with ST segment elevation myocardial infarction (STEMI) or non-STEMI (NSTEMI) versus unstable angina (UA). The primary endpoint was 1-year target lesion failure (TLF), composite of cardiac death, target vessel myocardial infarction, or clinically driven target lesion revascularization. Secondary outcomes included stent thrombosis (ST). RESULTS: We compared 1965 (54%) ACS and 1649 (46.0%) non-ACS patients. ACS presentations included 40% (n = 789) STEMI, 31% (n = 600) NSTEMI, and 29% (n = 576) UA patients. Risk of 1-year TLF was greater in ACS patients (4.5% vs. 3.3%, HR 1.51 95% CI 1.01-2.25, p = 0.045) without significant differences in definite/probable ST (1.1% vs 0.5%, HR 2.40, 95% CI 0.91-6.31, p = 0.08). One-year TLF was similar in STEMI, NSTEMI, and UA (4.8% vs 4.8% vs. 3.7%, p = 0.60), but definite/probable ST was higher in STEMI patients (1.9% vs 0.5% vs 0.7%, p = 0.03). Adjusted outcomes were not different in MI versus UA patients. CONCLUSIONS: Despite the novel EPC capture technology, COMBO stent PCI was associated with somewhat greater risk of 1-year TLF in ACS than in non-ACS patients, without significant differences in stent thrombosis. No differences were observed in 1-year TLF among ACS subtypes.
Keywords: Endothelial Progenitor Cells; Acute Coronary Syndrome; Prosthesis Design; Coronary Thrombosis; protézy - design; Time Factors; časové faktory; stenty uvolňující léky; lidé; Drug-Eluting Stents; koronární angioplastika; koronární trombóza; Risk Factors; Percutaneous Coronary Intervention; Sirolimus; rizikové faktory; Myocardial Infarction; Angina, Unstable; sirolimus; akutní koronární syndrom; endoteliální progenitorové buňky; nestabilní angina pectoris; infarkt myokardu; Humans